절단장애인을 위한 한국어 의지평가 설문지의 신뢰도 - 성우성(Woo-Sung Seong); 김장환(Jang-Hwan Kim); 정동훈(Dong-Hun Jeong) (디지털콘텐츠학회논문지, 2018)
한국어 의지평가 설문지를 개발하고 그 타당도가 연구되었으나, 다리 절단장애인을 대상으로 의지평가 설문지를 적용하여 신뢰도를 평가한 연구는 실시되지 않았다. 본 연구에서는 다리 절단장애인을 대상으로 개발된 한국어-PEQ를 적용하여 그에 대한 신뢰도를 평가하였다. 그 결과, 한국어-PEQ의 모든 항목에서 천장효과와 바닥효과가 15%이하로 나타나 응답의 난이도가 적절한 것으로 나타났다. 한국어-PEQ 영역별 신뢰도(inter-rater reliability)의 급간내 상관계수(intra-class coefficient, ICC)는 .719(95%CI .600~.811)~.920(95%CI .890~.945)로 나타났고, 영역간 신뢰도는 .958로 높게 나타났다. 문항 내적 일치도 Cronbach's α값은 .910으로 높게 나타나 한국어-PEQ는 높은 신뢰도가 있음을 알 수 있었다. Korean-PEQ (prosthesis evaluation questionnaire) was developed and verified its validity research but, evaluating its reliability applied to the lower extremity amputees have not been conducted. The aim of this study was to apply the Korean-PEQ for lower extremity amputees to evaluate the reliability. As a result, all of the items responding of Korean-PEQ shown to less than 15% ceiling effect and floor effect. therefore, the results were shown to be appropriate. Korean-PEQ reliability of each region of intra-class coefficient was shown to .719(95% CI .600~.811)~920(95%CI .890~.945) and the inter-region reliability was higher as 0.958. Item internal consistency Cronbach's α values are shown as higher .910. KCI Citation Count: 2